No increased mortality after total hip arthroplasty in patients with a history of pediatric hip disease: a matched, population-based cohort study on 4,043 patients - Miriam G Wadström (Taylor & Francis Group, 2021)
Background and purpose — Patients with pediatric hip diseases are more comorbid than the general population and at risk of premature, secondary osteoarthritis, often leading to total hip arthroplasty (THA). We investigated whether THA confers an increased mortality in this cohort. Patients and methods — We identified 4,043 patients with a history of Legg–Calvé–Perthes disease (LCPD), slipped capital femoral epiphysis (SCFE), or developmental dysplasia of the hip (DDH) in the Swedish Hip Arthroplasty Register (SHAR) between 1992 and 2012. For each patient, we matched 5 controls from the general population for age, sex, and place of residence, and acquired information on all participants’ socioeconomic background and comorbidities. Mortality after THA was estimated according to Kaplan–Meier, and Cox proportional hazard models were fitted to estimate adjusted hazard ratios (HRs) for the risk of death. Results — Compared with unexposed individuals, patients exposed to a THA due to pediatric hip disease had lower incomes, lower educational levels, and a higher degree of comorbidity but a statistically non-significant attenuation of 90-day mortality (HR 0.9; 95% CI 0.4–2.0) and a lower risk of overall mortality (HR 0.8; CI 0.7–0.9). Interpretation — Patients exposed to THA due to a history of pediatric hip disease have a slightly lower mortality than unexposed individuals. THA seems not to confer increased mortality risks, even in these specific patients with numerous risk factors.